IoT Applications in Agriculture: Enhancing Crop Yield in Vietnam - Thi, Pham (Asian Journal of Computing and Engineering Technology, 2024)
Purpose: To aim of the study was to analyze the IoT applications in agriculture: enhancing crop yield in Vietnam Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: IoT applications in agriculture have significantly enhanced crop yield in Vietnam. Through sensors and IoT devices, farmers monitor soil conditions like moisture, temperature, and humidity in real-time. This data-driven approach optimizes irrigation and fertilization, minimizing waste and maximizing resource efficiency. Studies show that smart farming techniques using IoT lead to higher crop yields by ensuring optimal growth conditions and timely pest and disease management. Remote monitoring also improves farm management, reducing labor costs and promoting sustainable practices through precise resource management. Unique Contribution to Theory, Practice and Policy: Technology acceptance model (TAM) & diffusion of innovations theory& resource-based view (RBV) may be used to anchor future studies on IoT applications in agriculture: enhancing crop yield in Vietnam. Encourage the adaptation and customization of IoT solutions to suit local farming practices and environmental conditions across different regions of Vietnam. Implement policies that incentivize the adoption of IoT technologies in agriculture, particularly among smallholder farmers.